2018
DOI: 10.1177/0960327118792050
|View full text |Cite
|
Sign up to set email alerts
|

Ferruginol induced apoptosis on SK-Mel-28 human malignant melanoma cells mediated through P-p38 and NF-κB

Abstract: In the present investigation, the antitumor effect of ferruginol (FGL) in SK-Mel-28 human malignant melanoma cells was studied. To investigate the cytotoxic property of FGL, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was used. Results revealed that prolonged treatment duration decreases the IC25, IC50, and IC75 concentrations of FGL. The cytotoxicity was further confirmed by lactate dehydrogenase assay. As evident f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…cells. These results agreed with investigations that reported that ferruginol inhibited the growth of ovarian carcinoma cells and melanoma cells [16,17]. Compounds of plant origin have been shown to halt the growth of cancer cells through multiple mechanisms such as apoptosis, cell cycle arrest, and autophagy [18].…”
Section: Discussionsupporting
confidence: 90%
“…cells. These results agreed with investigations that reported that ferruginol inhibited the growth of ovarian carcinoma cells and melanoma cells [16,17]. Compounds of plant origin have been shown to halt the growth of cancer cells through multiple mechanisms such as apoptosis, cell cycle arrest, and autophagy [18].…”
Section: Discussionsupporting
confidence: 90%
“…To sum up, we have carried out the first chemical synthesis of the abietane (+)-4-epi-liquiditerpenoic acid A (8a). It was prepared in a short synthetic sequence of five steps in 10% overall yield from methyl callitrisate (7). Two parallel routes led to several oxidized analogs, such as naturally occurring lambertic acid (13) or 19-hydroxyferruginol (14).…”
Section: Discussionmentioning
confidence: 99%
“…The tested compounds 8a and 9-16 were obtained from (+)-methyl callitrisate (7), which was obtained from callitrisic acid (6) extracted from Sandarac resin [18], as shown in Scheme 1. Compounds 8a, 15 and 16 are novel derivatives.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidation of the exact mechanism of action of four triterpenes from the roots of Salvia deserta showed that despite the strong antioxidant capacity of 93, it also kill parasites by inhibiting isopentenyl diphosphate condensation with the major target being farnesyl diphosphate synthase [110]. Studies to also understand the molecular basics of 94 shows a similar action like 80, but fragmentation of DNA strands has been described for diterpene 95 and 96 [111,112]. Inhibition of oxidative pathways particularly IFN-γ-related signaling by similar diterpenoid quinones isolated from the roots of Salvia officinalis has also been shown to prevent disease proliferation and further protecting the host specie [113].…”
Section: Terpenes and Terpenoidsmentioning
confidence: 99%